Efficacy and safety of intracervical Foley’s in women receiving sublingual misoprostol for induction of labour: a randomized controlled trial - Yadaraju, Salini; Chaturvedula, Latha; Rengaraj, Sasirekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Induction of labour can be carried out by medical or mechanical methods, used alone or in combination. This study is to evaluate the efficacy and safety of intracervical Foley’s in women receiving sublingual misoprostol for induction of labour. Methods: We randomized 230 primi gravidae at ≥37 weeks of gestation, with singleton pregnancy, cephalic presentation requiring induction, with Bishop score ≤4 using block randomization into study and control groups. Both groups received 50 µg sublingual misoprostol every fourth hourly till active labour was achieved or upto a maximum of 6 doses. The study group was induced simultaneously with intracervical Foley catheter. Results: Mean induction to labour interval in study and control groups was 11.191±7.14 hours and 11.758±6.26 hours while mean induction to delivery interval was 17.502±7.93 hours and 18.275±7.66 hours respectively with no significant difference between the groups (p=0.522 and 0.453). More women in study group than in the control (51.3% versus 33.9%) were in active labour within ten hours of induction (p=0.001). Caesarean section rate was 23.5% and 19.1% in study and control groups (p=0.497), the most common indication being foetal distress. Secondary outcomes like foetal heart rate abnormalities, oxytocin requirement were comparable between the two groups. APGAR scores and NICU admission rate were similar in both groups. There was no significant maternal or neonatal morbidity. Conclusions: Though there was no significant reduction in induction to labour or delivery interval with synchronous use of sublingual misoprostol and Foley’s, there was no increase in the complications encountered.